Reduction in plantar heel pain and a return to sport after a barefoot running intervention in a female triathlete with plantar fasciitis - Francis, P.; Oddy, C.; Johnson, M. I. (International Journal of Athletic Therapy & Training, 2017)
In a 27-year-old female triathlete, magnetic resonance imaging revealed mild thickening and edema at the calcaneal insertion of the plantar fascia, in keeping with a degree of plantar fasciitis. After 6 weeks of conservative treatment failed to elicit a return to sport, the patient engaged in six sessions of barefoot running (15-30 min) on a soft grass surface, without further conservative treatment. After two sessions of barefoot running, the patient was asymptomatic before, during, and after running. This outcome was maintained at the 6-week follow-up period. This is the first case report to use barefoot running as a treatment strategy for chronic heel pain. Barefoot running has the potential to reduce the load on the plantar fascia and warrants further investigation using a case series.